PEMOLAAN KOMUNIKASI TRADISI JALANG MENJALANG NINIK MAMAK KEMENAKAN: Studi Etnografi Komunikasi Pada Masyarakat Desa Ngaso Kecamatan UjungBatu Kabupaten Rokan Hulu - Lingga Saputra; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Tradition jalang menjalang ninik mamak kemenakan is a hereditary tradition that every nephew's grandchildren in the village of Ngaso together visiting ninik mamak, sorak, government in a place that has been arranged in such a way and there is a series of communicative events in carrying out tradition jalang menjalang. Tradition jalang menjalang ninik mamak kemenakan held as a mark of respect or uphold ninik mamak bye grandchildren's niece and keep the relationship between the ropes ninik mamak kemenakan located in Ngaso Village. The purpose of this study is to know the communicative situation, communicative events, and communicative acts in the tradition jalang menjalang ninik mamak kemenakan in Ngaso Village.The method used in this research is qualitative method with ethnographic approach of communication. Infoman in this research is tribal parents, ninik mamak, and niece. Techniques of collecting data using interviews, observation, and documentation.Based on the results of the research, the communicative situation of the traditional event jalang menjalang ninik mamak in outdoors that is a multipurpose field Ngaso Village and the present ninik mamak, tribal parents, cheers, government figures and children's grandchildren nephew. Communicative events jalang menjalang ninik mamak Includes Type of event is a type of greeting, traditional music, silek, tombok adat, prayers and eat together. Topics in the form of tribute and hospitality. Objectives and Functions for the sign of respect or uphold mamak, hospitality, and introduce the customs of Ngaso Village to the grandchild's grandchild. Participants namely ninik mamak, tribal parents, cheers, government figures and all the children's grandchildren every tribal nephew. Verbal and non-verbal Messaging. The contents of the message in the form of custom tombok give advice by ninik mamak to the children and grandchildren nephew and prayers. The sequence of action that is pot hammer, playing instrument calempong at night, picking compan jinni by dubalang, welcoming jinni kompek with silek, and process goes tradisi jalang menjalang mamak. nteraction rules are available when welcoming, welcoming jinny and at the time of the event menjalang ninik mamak. Norms there are norms of civility, mutual respect, religious and customary values. Communicative acts in the event jalang menjalang ninik mamak kemenakan that someone who leads the event or has the skills and understand the norms and values of customs prevailing in Ngaso Village.Keywords: Tradition Jalang Menjalang Ninik Mamak, Comunicative Situation, Communicative Events, Communicative acts, ethnography of communication.